PENGARUH METODE BERNYANYI TERHADAP HASIL BELAJAR MATEMATIKA (PERKALIAN) PESERTA DIDIK MADRASAH IBTIDAIYAH - Wafiqni, Nafia; Haryanti, Ferdinni (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
The basis for this review is that at MI Al-Mursyidiyyah, especially in class III A, they have not used singing techniques. Then at that time the side effect of learning science in class III MI Al-Mursyidiyyah, there were 1% who had bad math scores. The reason for this review is to see whether there is an effect of the method on the mathematics learning outcomes of grade III A students. This test is directed at MI Al-Mursyidiyyah Pamulang, South Tangerang in September – November 2020. An example of the analysis class is class III A, which consists of 34 students obtained by Purposive Sampling. The method used is Pre-Experimental with One Group Pretest-Posttest Design (single meeting plan with pretest and posttest). The instrument used in this study was a cognitive test in the form of multiple choice. The data analysis technique used in this research is the n-gain test using a predetermined formula, the normality test using Shapiro Wilk, the homogeneity test using ANOVA (Anlysis of variance), the paired t hypothesis test (Two Paired Samples Test). Based on the results of the t-test on the pretest and posttest of the experimental class with the results of the t-count value of 9.858 > t-table 2.034 or H0 is rejected and H1 is accepted. So that it can be said that there is an effect of utilization on the mathematics learning outcomes of students of class III A MI Al-Mursyidiyyah Pamulang, South Tangerang.